Existential Dilemma in Star Wars: Last Shot Novel by Daniel Jose Older - Muhammad Fadhil Nugroho; Rahayu Puji Haryanti (Universitas Islam Negeri Palopo, 2025)
This study investigates the existential dilemmas faced by Han Solo in Daniel José Older’s Star Wars: Last Shot, with a focus on how his struggles with identity, purpose, and responsibility as a father influence his actions and relationships. The research addresses the following questions: How do Han’s existential conflicts manifest in the narrative? In what ways do these struggles impact his relationship with his son, Ben Solo? Using a descriptive qualitative approach, selected passages from the novel are analyzed to identify manifestations of existential conflict, drawing on Matthew Ratcliffe’s theory of existential feelings to interpret Han’s moods and decision-making. Key findings indicate that Han’s lack of role models and emotional distance contribute to repeated mistakes and strained family bonds, particularly with Ben, whose sense of abandonment is illustrated through pivotal scenes. These unresolved issues are shown to play a significant role in Ben’s eventual transformation into Kylo Ren. The study underscores the importance of emotional presence and self-awareness in parenting, suggesting that existential dilemmas can have lasting intergenerational effects. Data was collected through close textual analysis of the novel. Limitations include the focus on a single fictional character, indicating the need for comparative studies in other works or real-life contexts.